Hydrodynamics of living fluids in microflows. - Mauá, Sara Malvar (2019)
The main contribution of the present work is the proposition of a framework for analysis of active suspensions using the Caenorhabditis elegans nematode as the living model. To do so, five different perspectives are used: kinematics, macro-reological, numerical, theoretical and micro-reological. First, a theoretical and experimental analysis of the kinematic motion of the nematodes suspended in a biological fluid is presented. Two different populations are examined: starving and well fed nematodes. We show that the relationship between the length of an individual nematode and the wavelength of its movement is linear and can be adjusted by a theoretical prediction proposed in this work. A deep discussion on propulsive mechanics based on a scale analysis that identifies three major forces acting on an individual nematode is made. In addition, we investigated the shear viscosity of Caenorhabditis elegans suspensions. The oscillatory shear experiments revealed an anomalous viscosity behavior with the variation of the volumetric fraction of suspension, ?. The effective viscosity of the suspension decreased with increasing nematode volumetric fraction at low concentrations. Based on the experimental data, a phenomenological equation for the effective viscosity of the suspension as a function of the volumetric fraction of particles is proposed. The collective behavior of the nematodes is also observed in linear regime through the difference of normal stresses. Finally, step strain tests are conducted to obtain the relaxation times. The presence of a negative active stress due to the nematoid driving behavior persists for a period of time, leading to a negative undershoot and an oscillatory behavior in the relaxation function. In order to propose a rheological model, simplifications are made in the model and immersed boundary method simulations are conducted in a flexible filament, varying the type of movement that it performs. It is observed that the presence of asymmetries in its undulating movement generates drastic changes on its kinematic responses. A rheological model as a function of filament orientation is proposed and validated with experimental data in linear regime. After validation of the proposed constitutive equation, the model is observed under the nonlinear regime of oscillatory shear, in which the rheological characterizations are made based on existing frameworks using Lissajous-Bowditch curves and Pipkin diagrams. Finally, a protocol for analysis of suspensions in a microrheometer is presented. Particles are added and tracked as unidirectional oscillatory shear (pulsatile flow) is applied. The velocity and shear rate profiles are obtained, as well as the rheological signals equivalent to the strain rate and stress. Signal analysis tools are used and an artificial intelligence system is proposed to remove the component added to the signal by unidirectional shear, aiming to reconstruct the signal with null temporal average and allowing the application of well known rheological theories, such as the decomposition of stresses in coefficients of Chebyshev, for the calculation of viscommetric quantities of compliances and fluidities. The major contribution of the study concerns the observation, characterization, modeling and simulation of a microsized animal that moves in different fashion, depending on the environment, and the surrounding fluid. The rheological properties analyzed, simuations performed and model proposed can be used for both production of artifitial microorganisms and control of living organisms. Moreover, this combination of analyses and techniques can be used to study any type of passive and active suspension providing new and conclusive results regarding the rheological characterization and the physical behavior of the particles.